INTEGRASI TEKNOLOGI DALAM KONSERVASI KEANEKARAGAMAN HAYATI MELALUI PEMBUATAN HERBARIUM DIGITAL DI SANGGAR BIMBINGAN WIRA DAMAI, BATU CAVES, SELANGOR, MALAYSIA - Dina Chamidah; Sunaryo; Dwi Haryanta; Marmi; Pramita Laksitarahmi Isrianto (UNIVERSITAS PGRI MADIUN, 2026)
Abstract. Biodiversity conservation requires educational approaches that integrate field-based learning with digital technology to enable learners to develop a contextual understanding of the importance of conserving biological resources. This community service program aimed to enhance participants' knowledge and skills in biodiversity conservation through the development of a web-based digital herbarium at Sanggar Bimbingan Wira Damai, Batu Caves, Selangor, Malaysia. The program employed a participatory approach consisting of conservation awareness sessions, flora exploration, species identification, digital documentation, digital herbarium development, website publication, and program evaluation. The participants included 20 individuals, comprising 16 students and 4 teachers. Program effectiveness was evaluated using pretest–posttest assessments, observation sheets, and participant response questionnaires. The results showed that the participants' mean score increased from 57.9 in the pretest to 82.4 in the posttest, with an N-Gain score of 0.58, indicating a moderate level of improvement. Observation results revealed that participants demonstrated good performance in specimen photography, plant identification, digital data processing, digital herbarium preparation, and presentation skills, with achievement scores ranging from 80% to 85%. The program also produced the Digital Herbarium Lovable.dev, a web-based digital herbarium that documents plant species together with their local names, scientific names, taxonomic classification, morphological characteristics, habitats, uses, and photographic records, providing a sustainable conservation-based learning resource. Overall, the program demonstrates that integrating digital technology into biodiversity conservation education can improve participants' understanding, enhance their digital literacy skills, and produce an innovative learning medium that supports the documentation and conservation of local biodiversity. Abstrak. Konservasi keanekaragaman hayati memerlukan pendekatan pembelajaran yang mampu mengintegrasikan aktivitas lapangan dengan pemanfaatan teknologi digital sehingga peserta didik dapat memahami pentingnya pelestarian sumber daya hayati secara kontekstual. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman dan keterampilan peserta mengenai konservasi keanekaragaman hayati melalui pengembangan herbarium digital berbasis website di Sanggar Bimbingan Wira Damai, Batu Caves, Selangor, Malaysia. Kegiatan dilaksanakan menggunakan pendekatan partisipatif melalui tahapan sosialisasi konservasi, eksplorasi flora, identifikasi spesies, dokumentasi digital, penyusunan herbarium digital, publikasi website, dan evaluasi kegiatan. Sasaran kegiatan terdiri atas 20 peserta, yaitu 16 siswa dan 4 guru. Evaluasi dilakukan menggunakan pretest–posttest, lembar observasi keterampilan, dan angket respon peserta. Hasil kegiatan menunjukkan bahwa nilai rata-rata peserta meningkat dari 57,9 pada pretest menjadi 82,4 pada posttest dengan nilai N-Gain sebesar 0,58 yang termasuk kategori sedang. Hasil observasi menunjukkan bahwa kemampuan peserta dalam pengambilan gambar spesimen, identifikasi tumbuhan, pengolahan data digital, penyusunan herbarium digital, dan presentasi berada pada kategori baik dengan capaian antara 80%–85%. Selain itu, kegiatan menghasilkan prototipe Digital Herbarium Lovable.dev, yaitu website herbarium digital yang memuat dokumentasi spesies tumbuhan beserta informasi nama lokal, nama ilmiah, klasifikasi taksonomi, karakter morfologi, habitat, manfaat, dan dokumentasi visual sehingga dapat dimanfaatkan sebagai media pembelajaran berbasis konservasi secara berkelanjutan. Kegiatan ini menunjukkan bahwa integrasi teknologi digital dalam konservasi keanekaragaman hayati mampu meningkatkan pemahaman peserta, mengembangkan keterampilan literasi digital, serta menghasilkan media pembelajaran yang mendukung dokumentasi biodiversitas lokal.